2016
DOI: 10.1007/s12665-016-5754-7
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and analysis of lithology heterogeneity on CO2 geological sequestration in deep saline aquifer: a case study of the Ordos Basin

Abstract: A simplified two-dimensional axisymmetric model was established based on a typical continental sedimentary basin in China to simulate the thermal evolution of wellbore and reservoir during the injection of CO 2 by taking consideration of lithology heterogeneity of reservoir. By comparing with two simple one-dimensional theory models, the lithology heterogeneity influence on CO 2 mass flow rate distribution along depth in the wellbore is identified. Results suggested that the interaction of multiple layers in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Due to magnitude difference of actual CO 2 injection rates throughout the screen interval, both viscous and buoyancy forces differently acted on CO 2 plume between Case 1 and Case 2 [44]. Furthermore, relatively warm CO 2 (e.g., 52…”
Section: Patterns For Salt-precipitation and Co 2 /Brine Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to magnitude difference of actual CO 2 injection rates throughout the screen interval, both viscous and buoyancy forces differently acted on CO 2 plume between Case 1 and Case 2 [44]. Furthermore, relatively warm CO 2 (e.g., 52…”
Section: Patterns For Salt-precipitation and Co 2 /Brine Flowmentioning
confidence: 99%
“…Most importantly, development of the localized salt was dependent on the degree of buoyancy force on CO 2 plume, which was governed by the injection rate and thermophysical properties of CO 2 . Even though thermophysical CO 2 properties could be changed significantly after CO 2 experiencing the wellbore processes, only a few studies were considered the wellbore processes impacting on CO 2 behavior in the storage formation [22,24,[43][44][45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of geohydrological, mechanical, thermal, and geochemical processes involved in Shenhua CCS project have been reported [29][30][31][32][33]. However, few of these have focused on the considerable CO 2 injectivity increase during CO 2 injection period.…”
Section: Introductionmentioning
confidence: 99%
“…However, few of these have focused on the considerable CO 2 injectivity increase during CO 2 injection period. Liu et al [33] examined this unique phenomenon through numerical simulation and concluded that it could be explained through heterogeneities in reservoir permeability. However their approach did not consider the possible role of CO 2 -water-rock interactions on CO 2 injectivity.…”
Section: Introductionmentioning
confidence: 99%